Effect of Castanopsis megacarpa Extract on Mortality, Longevity Development and Feeding of Crocidolomia pavonana Larvae - Edy Syahputra; Kukuh Hernowo; Riko Riko (AGRIVITA, Journal of Agricultural Science, 2019)
As several reports of impacts arise due to the use of synthetic insecticides, the investigation for safer alternative insecticides should be continued. Using plant material that has several bioactivities is a promising way out to control insect pest. The objective of this study was to evaluate the effect of leaf and seed extract of Castanopsis megacarpa on mortality, longevity development and feeding preference of Crocidolomia pavonana larvae. Extraction conducted by infusion method. The bioassay assesment was carried out using the residual method. The concentration-mortality relationship was analyzed by probit. The antifeedant test was tested using choice and no-choice methods. Both extracts showed the same strong insecticidal activity, LC50 of 0.18% (leaf) and 0.12% (seed). Leaf and seed extracts at concentrations equivalent to LC50 and LC75 in both methods used showed consistent antifeedant properties. The antifeedant activity of extracts in the no-choice method at both concentrations showed a range of activities of 40.1%-53.7% (leaf) and 74.4%-82.7% (seed) extracts. The leaf and seed extracts of C. megacarpa did not significantly extend the larval development period. Plant material that has more than one bioactivity will be better for suppress the insect pest populations in the field.